Exploring the Diversity of Arbuscular Mycorrhizal Fungi in Zingiberaceae Family Plants at the Tukung Gede Mountain Natural Reserve - Rida Khastini; Iing Dwi Lestari; Indah Juwita Sari; Nida Septiani (Journal of Tropical Biodiversity and Biotechnology, 2025)
Arbuscular mycorrhizal fungi (AMF) are essential in improving soil quality and facilitating plant nutrient and water uptake through mutualistic associations. However, limited research exists on the diversity and distribution of AMF associated with plants in the Zingiberaceae family, especially in unique ecological habitats such as the Tukung Gede Mountain Natural Reserve. This study aims to assess and document the diversity of AMF linked to Zingiberaceae plants in this reserve. Sampling was performed at three locations with distinct plant compositions to explore the diversity of AMF genera. Soil samples were processed using a wet sieve technique, while root samples were chemically stained to evaluate AMF colonization. Key parameters studied included diversity indices, spore density, genus-level identification, and root colonization rates. The findings revealed the presence of eight AMF genera: Sclerocystis, Septoglomus, Acaulospora, Gigaspora, Glomus, Scutellospora, Racocetra, and Rhizophagus, identified based on spore morphology. Root staining revealed structural AMF infections, including vesicles, internal hyphae, and arbuscules. Zingiber officinale exhibited the highest AMF colonization rate (88%) among the Zingiberaceae plants studied, whereas Zingiber zerumbet had the lowest (56%). Etlingera Solaris and Zingiber officinale showed the highest spore densities at 172 and 254 spores per 100g of soil, respectively. AMF diversity indices varied across locations, with values of 0.78 (Station I), 0.95 (Station II), and 0.84 (Station III). This research emphasizes the extensive AMF diversity within Zingiberaceae plants and its potential importance for conservation and ecological sustainability.